Training on Making Cooperation Proposals and Tour Guides for Purbayan Tourism Village Management, Kotagede, Yogyakarta - Bambang Robi'in; Arif Ardy Wibowo; Vera Yuli Erviana; Iis Suwartini; Gibbran Prathisara (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This community service aims to strengthen The Purbayan Tourist VIillage about cooperation proposals and tour guides. The Purbayan Tourist Village boasts a diverse range of tourism potential, spanning from craft tourism, historical tourism, culinary tourism, to exploring cultural heritage sites. This diverse tourism potential necessitates effective management of the Purbayan Tourist Village. The existing challenge lies in relying on tourists to visit the Purbayan Tourist Village and a lack of understanding in the tour guiding process. Community engagement is targeted towards the Purbayan Tourist Village management to be more proactive in attracting tourists by offering collaboration proposals to potential agencies and implementing added value through tour guides. The community engagement methodology began with preparation and socialization on August 5, 2023. It was followed by a collaboration proposal-making training on August 12-13, 2023. Next was the tour guide training on September 29, 2023, culminating in an evaluation for improvement and performance enhancement in the future. The results of the conducted training showed an increase in understanding the collaboration proposal-making process and tour guiding. Both trainings received positive responses from the Purbayan Tourist Village management, with an understanding increase of 58.21% for the collaboration proposal-making training and 46.05% for the tour guide training. With these two trainings, the Purbayan Tourist Village management will be better prepared to develop the existing tourism potential in the Purbayan Sub-district and drive the local economy for the surrounding community.